2016
DOI: 10.1111/aor.12666
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Rotational Speed Modulation System Used With an Implantable Continuous‐Flow Left Ventricular Assist Device on von Willebrand Factor Dynamics

Abstract: We have developed a rotational speed (RS) modulation system for a continuous-flow left ventricular assist device (EVAHEART) that can change RS in synchronization with a patient's electrocardiogram. Although EVAHEART is considered not to cause significant acquired von Willebrand syndrome, there remains a concern that the repeated acceleration and deceleration of the impeller may degrade von Willebrand factor (vWF) multimers. Accordingly, we evaluated the influence of our RS modulation system on vWF dynamics. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Thus, the significant differences observed during these in vitro VWF-compatibility tests of the HMII and HVAD suggest VWF multimer and functional changes may be a more sensitive indicator of shear-related blood trauma than clinical non-surgical bleeding rates. The results of VWF-compatibility testing of the EVAHEART VAD supports the proposition that benchtop testing 18,19 reflected clinical results 20,21 . We observed that the Levacor preserved VWF function and multimer distribution; however, this device is no longer in use and clinical VWF-compatibility and bleeding rates have not been published.…”
Section: Discussionsupporting
confidence: 65%
“…Thus, the significant differences observed during these in vitro VWF-compatibility tests of the HMII and HVAD suggest VWF multimer and functional changes may be a more sensitive indicator of shear-related blood trauma than clinical non-surgical bleeding rates. The results of VWF-compatibility testing of the EVAHEART VAD supports the proposition that benchtop testing 18,19 reflected clinical results 20,21 . We observed that the Levacor preserved VWF function and multimer distribution; however, this device is no longer in use and clinical VWF-compatibility and bleeding rates have not been published.…”
Section: Discussionsupporting
confidence: 65%
“…Normal human plasma (NP, Siemens Healthineers, Erlangen, Germany) was also electrophoresed, as a control. The gel was blotted on membrane and detected using anti-vWF primary antibody (Agilent DAKO, Carpinteria, California, USA) and IRDye 800CW-labeled anti-rabbit IgG secondary antibody (LI-COR Bioscience, Lincoln, NE, USA) as previously described (Naito et al, 2016).…”
Section: Vwf Multimer Analysismentioning
confidence: 99%
“…(A) VWF multimer analysis (upper) using human normal plasma (NP, GCH-100A; Sysmex, Kobe, Japan). The mobility (distance from the gel top) of each band (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and the distance between adjacent bands (lower) showed band 1 (magenta) behaved differently from band 2 (cyan, dimer) and the other bands (black). (B) The agarose gel after electrophoresis of NP was cut into 24 pieces from top to bottom (left).…”
Section: Introductionmentioning
confidence: 99%